Effects of Peers and Rank on Cognition, Preferences, and Personality - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (Global Labor Organization (GLO), 2020)
We exploit the variation in admission cutoffs across colleges at a leading Indian university to estimate the causal effects of enrolling in a selective college on cognitive attainment, economic preferences, and Big Five personality traits. Using a regression discontinuity design, we find that enrolling in a selective college improves university exam scores of the marginally admitted females, and makes them less overconfident and less risk averse, while males in selective colleges experience a decline in extraversion and conscientiousness. We find differences in peer quality and rank concerns to be driving our findings.
Keywords: I23; C9; C14; J24; O15; 330; College Quality; Peer Effects; Rank Concerns; Regression Discontinuity; India